2014
DOI: 10.14348/molcells.2014.0001
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Mechanism for Binding of p53 DNA-Binding Domain and Anti-Apoptotic Bcl-2 Family Proteins

Abstract: The molecular interaction between tumor suppressor p53 and the anti-apoptotic Bcl-2 family proteins plays an essential role in the transcription-independent apoptotic pathway of p53. In this study, we investigated the binding of p53 DNA-binding domain (p53DBD) with the anti-apoptotic Bcl-2 family proteins, Bcl-w, Mcl-1, and Bcl-2, using GST pull-down assay and NMR spectroscopy. The GST pull-down assays and NMR experiments demonstrated the direct binding of the p53DBD with Bcl-w, Mcl-1, and Bcl-2. Further, NMR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…The interactions between BCL-w and poorly characterized members of the BCL-2 family, BFK 20 and BOP 21 have also been reported. Moreover, α1/2 and α5/6 loops of BCL-w can associate with p53 through p53 DNA-binding domain, which contributes to transcription-independent regulation of cell death 22 . BCL-w also interacts with BH3-like domain of Beclin-1, an autophagy-related protein 23 .…”
Section: Introductionmentioning
confidence: 99%
“…The interactions between BCL-w and poorly characterized members of the BCL-2 family, BFK 20 and BOP 21 have also been reported. Moreover, α1/2 and α5/6 loops of BCL-w can associate with p53 through p53 DNA-binding domain, which contributes to transcription-independent regulation of cell death 22 . BCL-w also interacts with BH3-like domain of Beclin-1, an autophagy-related protein 23 .…”
Section: Introductionmentioning
confidence: 99%
“…The association between afatinib and the Bcl-2 protein family was further investigated. The Bcl-2 protein family comprises pro-apoptotic (Bax) and anti-apoptotic (Bcl-2) proteins that modulate permeabilization of the mitochondrial outer membrane and caspase activation in the control of apoptosis (16). The present study indicates that afatinib treatment upregulates the pro-apoptotic protein Bax and downregulates the anti-apoptotic protein Bcl-2.…”
Section: Discussionmentioning
confidence: 50%
“…The p53 gene, encoding a transcriptional factor, may induce apoptosis of tumor cells and serve as a tumor suppressor gene. The Bcl-2 protein, a member of the Bcl-2 family, may inhibit the cell apoptosis in a number of types of cancer ( 47 ). In the present study, expression of JNK2 and the phosphorylation protein p-JNK2 were upregulated by the overexpression of miR-146a, which indicated that JNK2 may be activated by miR-146a.…”
Section: Discussionmentioning
confidence: 99%